2016
DOI: 10.5114/aic.2016.59364
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary artery rupture as a complication of Swan-Ganz catheter application. Diagnosis and endovascular treatment: a single centre’s experience

Abstract: IntroductionThe placement of a Swan-Ganz catheter into the pulmonary artery may lead to a number of complications (2–17%). In less than 0.2% of cases Swan-Ganz catheterization results in serious vascular damage – pulmonary artery rupture (PAR). This paper presents two distinct forms of iatrogenic PAR treated endovascularly using different vascular devices.AimTo evaluate the effectiveness of endovascular treatment and the application of different types of vascular devices in the management of pulmonary artery r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 20 publications
0
21
0
2
Order By: Relevance
“…Furthermore, PA injury induced by a PA catheter has been reported, particularly by Swan-Ganz catheters. [15][16][17] This may be caused by over-inflation of the balloon or inadvertent partial inflation of the balloon in a small branch vessel. When performing the UPAO test in patients with pulmonary hilar tumours, the possibility of tumour invasion to the right or left PA needs to be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, PA injury induced by a PA catheter has been reported, particularly by Swan-Ganz catheters. [15][16][17] This may be caused by over-inflation of the balloon or inadvertent partial inflation of the balloon in a small branch vessel. When performing the UPAO test in patients with pulmonary hilar tumours, the possibility of tumour invasion to the right or left PA needs to be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, another meta-analysis found that SGC-guided management did not improve the mortality rate or cost-effectiveness for adult HF patients in intensive care ( 16 ). However, we cannot ignore the complications associated with SGC ( 2 ), and the advantages of monitoring circulation by SGC are weakened by those complications. Following the publication of these SGC meta-analyses, Chatterjee reviewed the indications for the use of SGC and determined that routine SGC in high-risk cardiac and noncardiac patients is not recommended ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, SGC is invasive, expensive, and labor-intensive. Major risks of an SGC procedure include bruising at the site of insertion, excessive bleeding, and vein injury, and minor risks include blood clots, low blood pressure, arrhythmias, cardiac tamponade, and pulmonary artery rupture, a rare occurrence with a 50% mortality rate ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, arrhythmias are reported in previous studies in a similar percentage [ 14 ]. Frequency of adverse events, especially more serious, appear mainly in research in which a greater number of patients was taken into consideration [ 9 , 13 , 14 , 33 ]. Complications such as artery puncture with/without insertion of a vascular sheath depend on access site and operator’s experience.…”
Section: Discussionmentioning
confidence: 99%